Efektivitas Formula Bacillus subtilis TM4 untuk Pengendalian Penyakit pada Tanaman Jagung - Nurasiah Djaenuddin; Nurnina Nonci; Amran Muis (Jurnal Fitopatologi Indonesia, 2017)
Banded leaf and sheath blight (BLSB) and maydis leaf blight (MLB) caused by Rhizoctonia solani and Bipolaris maydis, respectively are considered as important diseases in maize.   The use of biopesticides is an alternative method to control the diseases. This study was conducted to determine the effectiveness of bacterial formula Bacillus subtilis to inhibit the development of BLSB and MLB on the plant. Testing of biopesticide formula was done in two different applications, i.e. seed treatment for BLSB control and leaf spraying in the field for MLB. The results showed that the B.subtilis formula effectively suppressed the development of BLSB but it was not effectively suppressed the development of MLB .Key words: Bacillus subtilis, biopesticide, Bipolaris maydis, leaf blight diseaseBanded leaf and sheath blight (BLSB) and maydis leaf blight (MLB) caused by Rhizoctonia solani and Bipolaris maydis, respectively are considered as important diseases in maize.   The use of biopesticides is an alternative method to control the diseases. This study was conducted to determine the effectiveness of bacterial formula Bacillus subtilis to inhibit the development of BLSB and MLB on the plant. Testing of biopesticide formula was done in two different applications, i.e. seed treatment for BLSB control and leaf spraying in the field for MLB. The results showed that the B.subtilis formula effectively suppressed the development of BLSB but it was not effectively suppressed the development of MLB.